2017
DOI: 10.4028/www.scientific.net/msf.897.501
|View full text |Cite
|
Sign up to set email alerts
|

Understanding High Temperature Static and Dynamic Characteristics of 1.2 kV SiC Power MOSFETs

Abstract: High temperature capability of silicon carbide (SiC) power MOSFETs is becoming more important as power electronics faces wider applications in harsh environments. In this paper, comprehensive static and dynamic parameters of 1.2 kV SiC MOSFETs have been measured up to 250°C. The electrical behaviors with the temperature have been analyzed using the basic device physics and analytical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…[4]. Moreover, supported by the off-state measurements it has been suggested that the temperature dependence of power MOSFET's ITCs is weak [5]. As shown in [6], direct measurements of the ITCs with standard equipment are possible only at low current levels (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…[4]. Moreover, supported by the off-state measurements it has been suggested that the temperature dependence of power MOSFET's ITCs is weak [5]. As shown in [6], direct measurements of the ITCs with standard equipment are possible only at low current levels (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…5 (without considering the interface-trapped charge). With temperature increasing, the output current decreases due to a reduction in carrier mobility at higher temperature caused by the lattice scattering [32]. With increasing k value, the output current also decreases.…”
Section: A Optimization Of K Value Of the Insulation Pillarmentioning
confidence: 99%
“…The MOSFET switching transients have been analyzed extensively in literature, observing the impact of the stray inductances seen from the drain, source and gate terminals [7], the threshold voltage, and the MOSFET transconductance [8]. However, the individual influence of the non-linear voltagedependent drain-source capacitances C ds and drain-gate capacitance C dg is still unclear.…”
Section: Literature Surveymentioning
confidence: 99%